Tilted long period gratings pressure sensing in solid core photonic crystal fibers - Zhang, Yifan (2013)
A photonic crystal fiber pressure sensor using mechanical induced tilted long period grating is reported. Transmission dip has a blue shift when the tilted angle of the long period grating increases. The performances of the pressure sensor are evaluated by the shifting of the transmission spectrum after applying different pressure level. The experimental results show that the larger the tilted angle of the grating, the transmission dip experiences the larger blue-shift, leading to higher sensitivity up to 2.701 nm/MPa.